2021
DOI: 10.7324/japs.2021.110518
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the vasodilatory activity of ethanol extracts of Eleutherine bulbosa bulbs and leaves

Abstract: The aim of this study was to examine and compare the vasodilatory activities of ethanol extracts of Eleutherine bulbosa bulbs (EBBs) and leaves (EBLs) on isolated aortas from Wistar rats, with and without endothelium. EBBs and leaves EBLs were washed with clean water and chopped and dried in a 60°C drying cabinet. Extraction was carried out by maceration using an ethanol solvent. The collected filtrate was concentrated using a vacuum evaporator, and the concentrated liquid was dried further in a 60°C oven. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Several studies have shown that quercetin has positive effects on cardiovascular diseases. Suri et al evaluated the impact on vasoconstrictor and vasodilator reactions in the porcine heart, reporting that quercetin increased both cyclic guanosine mono-phosphate (cGMP) content and cGMP-dependent relaxations to glyceryl trinitrate (GTN) and sodium nitroprusside (SNP), as well as porcine receptor-mediated restrained contractions [ 45 ]. Also, a study with rats showed that quercetin (0.1–100 μM) relaxed the contraction induced by pretreatment with five mM norepinephrine in a concentration-dependent manner.…”
Section: Quercetin Particularitiesmentioning
confidence: 99%
“…Several studies have shown that quercetin has positive effects on cardiovascular diseases. Suri et al evaluated the impact on vasoconstrictor and vasodilator reactions in the porcine heart, reporting that quercetin increased both cyclic guanosine mono-phosphate (cGMP) content and cGMP-dependent relaxations to glyceryl trinitrate (GTN) and sodium nitroprusside (SNP), as well as porcine receptor-mediated restrained contractions [ 45 ]. Also, a study with rats showed that quercetin (0.1–100 μM) relaxed the contraction induced by pretreatment with five mM norepinephrine in a concentration-dependent manner.…”
Section: Quercetin Particularitiesmentioning
confidence: 99%
“…Several studies have shown that quercetin has positive effects on cardiovascular diseases. Suri et al evaluated the impact on vasoconstrictor and vasodilator reactions in the porcine heart, reporting that quercetin increased both cyclic guanosine mono-phosphate (cGMP) content and cGMP-dependent relaxations to glyceryl trinitrate (GTN) and sodium nitroprusside (SNP), as well as porcine receptor-mediated restrained contractions [45]. Also, a study with rats showed that quercetin (0.1-100 µM) relaxed the contraction induced by pretreatment with five mM norepinephrine in a concentration-dependent manner.…”
Section: Cardiovascular Protectionmentioning
confidence: 99%

Quercetin, A Flavonoid With Great Pharmacological Capacity

Carrillo-Martinez,
Flores-Hernández,
Salazar-Montes
et al. 2024
Preprint
“…Several studies have shown that Quercetin has positive effects on cardiovascular diseases. Suri et al evaluated the impact on vasoconstrictor and vasodilator reactions in the porcine heart, reporting that Quercetin increases both Cyclic Guanosine Mono-phosphate (cGMP) content and cGMPdependent relaxations to Glyceryl Trinitrate (GTN) and Sodium Nitroprusside (SNP), as well as porcine receptor-mediated restrained contractions [45]. Also, a study with rats showed that Quercetin (0.1-100 μM) relaxed the contraction induced by pretreatment with five mM norepinephrine in a concentration-dependent manner.…”
Section: Cardiovascularmentioning
confidence: 99%